2006
DOI: 10.1080/01443410500341304
|View full text |Cite
|
Sign up to set email alerts
|

Ways of Knowing and Epistemological Beliefs: Combined effect on academic performance

Abstract: To obtain a more complete understanding of personal epistemology this study examines two epistemic paradigms -ways of knowing (specifically connected knowing and separate knowing) and epistemological beliefs (specifically beliefs about knowledge structure, knowledge stability, learning speed, and learning ability). Participants were 107 college students who completed questionnaires that assessed ways of knowing and epistemological beliefs. Multivariate analysis of variance revealed that men score significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 18 publications
4
60
1
7
Order By: Relevance
“…The objectivist reflection of teaching-learning conception characterized with traditional concept [48]. The results of this study supported previous conceptual studies [21,32,71,80] and some researches' results [13,85] in literature. For instance, Aypay [ found that there is a negative and low relationship between BOTT and CTC, and there is a positive and moderate relation with TTC.…”
Section: Conclusion and Recommendationssupporting
confidence: 80%
“…The objectivist reflection of teaching-learning conception characterized with traditional concept [48]. The results of this study supported previous conceptual studies [21,32,71,80] and some researches' results [13,85] in literature. For instance, Aypay [ found that there is a negative and low relationship between BOTT and CTC, and there is a positive and moderate relation with TTC.…”
Section: Conclusion and Recommendationssupporting
confidence: 80%
“…Oysaki üniversite eğitimi boyunca eğitimin ilk yılları ile son yılları arası öğrencilerin bilimsel epistemolojik inançlarında olgunlaşma/gelişme beklenir (Hofer (2004a). Literatüre bakıldığında pek çok araştırmacının (Schommer-Aikins, Duell ve Hutter, 2005;Schommer-Aikins, 1990, 1994Schommer-Aikins ve Easter, 2006;Chan ve Elliott, 2002Braten ve Stromso, 2005Perry, 1970;King ve Kitchener, 1994;, Baxter-Magolda,1992;Belenky ve arkadaşları, 1986) bireylerin epistemolojik inançlarının, eğitim düzeyi vb. özelliklerine göre ardışık bir gelişim gösterdiğini öne sürdükleri görülmektedir.…”
Section: Tartişma Ve Sonuçunclassified
“…Perry discovered participants' personal epistemology developed from a belief that knowledge is handed down by authority, to a belief that knowledge is tentative and gathered over time through reason and empirical investigation (Schommer-Aikins & Easter, 2006). However, other researchers felt Perry's work did not fully explain the development of epistemological beliefs and conducted further research to advance understanding (Belenky et al, 1986;Schommer-Aikins, 2004;Schommer-Aikins & Easter, 2006. Belenky et al (1986) studied the perspective of women on the nature of knowledge, truth, and authority.…”
Section: Theoretical Framementioning
confidence: 99%